2010
DOI: 10.1111/j.1474-9726.2010.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

HRAS1 and LASS1 with APOE are associated with human longevity and healthy aging

Abstract: SummaryThe search for longevity-determining genes in human has largely neglected the operation of genetic interactions. We have identified a novel combination of common variants of three genes that has a marked association with human lifespan and healthy aging. Subjects were recruited and stratified according to their genetically inferred ethnic affiliation to account for population structure. Haplotype analysis was performed in three candidate genes, and the haplotype combinations were tested for association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 52 publications
2
64
0
Order By: Relevance
“…Accordingly, the molecular signatures of ADs are consistent with the cis‐(haplotype) rather than a single allele origin of ADs (Jazwinski et al., 2010; Lescai et al., 2011). Whether the molecular signatures of ADs include the APOE, e4 allele remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the molecular signatures of ADs are consistent with the cis‐(haplotype) rather than a single allele origin of ADs (Jazwinski et al., 2010; Lescai et al., 2011). Whether the molecular signatures of ADs include the APOE, e4 allele remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies in this area have focused on elucidating the genetic basis of heritable variation in age-specific mortality and longevity (Dudycha and Tessier 1999;Guarente and Kenyon 2000;Wilson et al 2007Wilson et al , 2008Blomquist 2010;Fontana et al 2010) and several candidate genes contributing to this variation have been identified (De Luca et al 2003;Burger and Promislow 2006;Paaby and Schmidt 2008;Jazwinski et al 2010;Soerensen et al 2010). In contrast, we know little about the genes that influence age-related functional declines in life history or physiological traits that may in turn affect age-specific mortality and limit life span (Burger and Promislow 2006;Charmantier et al 2006;Leips et al 2006;Lesser et al 2006;Nussey et al 2008a).…”
mentioning
confidence: 99%
“…Indeed, there are many inconsistencies with the notion that rDNA circles are an important factor in yeast aging, and there is significantly more support for the instability of rDNA itself as the critical factor (Ganley and Kobayashi 2014). There is also support for the notion that excessive transcription of rDNA during aging may play a role (Kim et al 1999;Jazwinski 2000;Jazwinski et al 2010;Stumpferl et al 2012), and this may be related to the regulation of protein translation in the cytoplasm (Steinkraus et al 2008). Thus, there remains much to learn about the role of different DNA transactions at the rDNA locus in yeast replicative aging.…”
Section: Discussionmentioning
confidence: 99%